(untitled) (Baghdad Science Journal, 2025)
Infertilityis oneuof the most problemsathatufacingaadvancedunations. In the general, about halfof allacasesaof the infertility are causedby factors thaturelated toathe male partner. Propos educausesvofumalev infertility include evgeneticuand environmental factors. Blood samples from 64 infertileumen allawere living in urban its al-Fallujah city (30 azospermeiauand 34 oligospermeia) and 32 fertile men (asuthe control group) were collected. Heavy metal concentrations inusera of infertile and fertile groupswereumeasured by using Atomic Absorption Spectrophotometer. Y- chromosomemicrodeletions were detected by using PCR techniques. Significantdifferences (P?0.05)uin the concentration ofucopper (0.0267±0.0147 and 0.0278±0.0273, for infertileuand fertile group respectively), cadmium (0.0477± 0.0038 and 0.0446±0.0059, respectively) and zinc (1.08 ± 0.16) in fertile groupamoreover wereadetected, no deletionsawere recorded in Y Chromosome in peopleuwho exposed to heavy metals in each a azospermiavor severe oligospermia groups. Spermatogenesis disruption in theamale at any phase of cell differentiationamay be increased the abnormaluof sperm count also decrease theutotalspermucount, impair the stability of sperm chromatinuordamageain the sperm DNA.